850 Longitudinal study of motor vehicle crash rates among licensed teen drivers with adhd. (1st September 2016) - Curry, Allison E; Metzger, Kristina B; Pfeiffer, Melissa R; Winston, Flaura K; Elliott, Michael R; Power, Thomas
Abstract : Background: Several small studies suggesting teens with ADHD are at heightened crash risk were conducted among more severely affected teens in highly specialised samples but had substantial methodological limitations. Thus, we conducted the first truly longitudinal study focused on comparing crash risk between teen drivers with and without ADHD. We also aimed to determine if the association between ADHD and risk varies by sex, licensing age, or over the course of licensure. Methods: We utilised electronic health records (EHR) to identify residents of New Jersey (NJ) born 1987–1995 who were patients of The Children's Hospital of Philadelphia's six NJ primary care practices within 4 years of driving-eligible age. EHR records were linked to NJ's state-wide driver licensing and crash databases through June 2012. Subjects were classified as having ADHD using ICD-9-CM diagnosis codes and known chronic conditions from their EHR. Cox regression was used to estimate adjusted hazard ratios (HR) to compare crash rates for 1, 307 licensed teens with and 10, 415 licensed teens without ADHD. Results: Subjects had a median [interquartile range] of 17 [9, 28] CHOP primary care visits, were 18 [16, 19] years old at their last visit, and were 21 [19, 23] years old at study end. Overall, the crash rate for teens with ADHD was 35% higher (95% CI: 1.22, 1.49) than for teens without ADHD. Modelling revealed heightened risk for male teens (HR [95% CI]: 1.43 [1.27, 1.61]) with less evidence of an increase among females (1.17 [0.97, 1.42]). Conversely, the association between ADHD and crash involvement did not vary by licensing age or over time. Conclusions: Young novice drivers with ADHD–and in particular males–appear to be at increased crash risk, although the estimated increase is notably lower than frequently cited figures from previous small studies of self-reported crashes. Additional research is needed to understand the specific mechanisms by which ADHD influences per-driver crash risk.